A CONTRIBUTION TO COLLABORATIVE RENEWABLE ENERGY COMMUNITIES - Adu-Kankam, Kankam Okatakyie (2024)
The notions of Collaborative Energy Ecosystem (CEE) and Cognitive Household Digital Twins (CHDTs) are proposed as two complementary and prospective concepts that could contribute to the efficient organization and management of emerging Renewable Energy Communities (RECs). The CEE concept was derived from the merger of principles and concepts from the disciplines of Collaborative Networks and Virtual Power Plants and is proposed as a representation of a REC, where members approach energy conservation (generation and consumption) from a collaborative point of view. The notion of CHDTs is also proposed as a digital twin representation of the constituent households of a CEE. It is further suggested that CHDTs could have the form of software agents within the cyber space and could be designed to possess some autonomous and cognitive capabilities which could enable them to play complimentary roles as decision-making agents within the corresponding physical households. The decisions of these agents are expected to promote collaborative behaviours that could increase the survivability and sustainability of the CEE. In this thesis, we use software simulation to demonstrate the feasibility of the CEE and CHDT concepts. We further show that through the cognitive capabilities of CHDTs, behaviours such as collaborative generation and consumption of energy could be achieved. Other behaviours, such as mutual influence and the ability to adopt some form of social innovation, are also shown. We adopted the Design Science Research Method by developing a software model (an artifact) of the CEE and its constituent CHDTs using a multi-paradigm simulation technique that involves the integration of System Dynamics, Agent-Based, and Discrete Event simulation techniques on a single platform. The thesis's outcome suggests that these concepts could be useful for managing the sustainability of CEEs or RECs.